SEER study of ablation versus partial nephrectomy in cT1A renal cell carcinoma. (25th June 2018) - Zhou, Minerva; Mills, Abigail; Noda, Christopher; Ramaswamy, Raja; Akinwande, Olaguoke
Aim: Compare ablation versus partial nephrectomy (PN) in T1A renal cell carcinoma (RCC) treatment, using the SEER database.Methods: Patients with diagnosed T1A RCC from 2004 to 2013 were identified. Propensity matching paired subjects with similar background variables. Kaplan–Meier and Cox proportional hazards regression were performed before and after matching.Results: Cohort included 4592 patients (809 ablation, 3783 PN). PN compared with ablation group had significantly increased overall survival (OS; 93.6% vs 81.9% 5-year survival; p < 0.0001) and cancer-specific survival (CSS; p < 0.0001). After matching (1222 pairs), PN group had significantly increased OS (91.0% vs 86.3% 5-year survival; p = 0.0457) but similar CSS (p = 0.4023).Conclusion: Ablation offers similar CSS but lower OS as PN for T1A RCC in this SEER database.